TREATMENT EFFECTIVENESS ANALYSIS OF OUTPATIENTS WITH ARTERIAL HYPERTENSION PLUS CORONARY HEART DISEASE IN UKRAINE - V. N. Kovalenko; M. I. Lutai (Евразийский Кардиологический Журнал)
The analysis of quality of the survey and using of drug therapy in patients with coronary heart disease with concomitant hypertension in outpatient clinics of large cities in Ukraine was conducted in the PRESTIGE study. Methods for evaluation of patients included: ECG at rest (98.3%), echocardiography (83.7%), ambulatory ECG monitoring (47.8%), test with dosed physical load (24.4%), ambulatory blood pressure monitoring (28.7%), coronary angiography (20.0%), determining of microalbuminuria and glomerular filtration rate (21.9 and 13.8% respectively). Analysis of medical prescriptions in the PRESTIGE study suggests that the choice of the main groups of drugs and drugs used in clinical practice is very close to international standards. The frequency of use of antithrombotic and lipid-lowering (statin) agents, BB and ACE inhibitors (medicines that improve the prognosis of patients with coronary artery disease) are comparable with data from recent international registers. However, the effectiveness of therapy in the light of generally accepted criteria remains critically insufficient. Despite treatment, the target cholesterol was achieved in only 23% of patients, and target levels of blood pressure (130/85 mm Hg) in only 12.5% of patients. In 63.4% of patients, including those receiving BB, heart rate remained more than 70 bmp. Referai of patients with CHD to myocardial revascularization should be recognized as passive tactic and the number of interventions performed is inadequate. Factors that could enhance the efficacy of therapy would be the application of adequate doses of drugs, monitoring and control for achieving of target levels of key indicators (LDL cholesterol, blood pressure, heart rate), as well as increasing patients' adherence to treatment.